PREVALENCE AND DETERMINANTS OF UNDIAGNOSED HYPERTENSION AMONG SLUM DWELLERS: A COMMUNITY-BASED CROSS-SECTIONAL SURVEY - RAJSINH MOHITE; VAISHALI MOHITE (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The objectives of the study were to determine the prevalence and determinants of undiagnosed hypertension (HTN) in slum population and to its strength of association. Methods: A community-based cross-sectional survey was conducted at Karad urban slum area of district Satara, India in the year 2018. The study was conducted among randomly selected 460 adults were in age ranges from 18 to 60 years. A standard World Health Organization-stepwise approach questionnaire includes demographic data, behavioral information, and clinical examination; anthropometric data were employed to elicit the data from the eligible study participants by interview and examination method. Inferential statistics were worked out to determine the significant statistical association among variables under study. Results: The prevalence of HTN among adult slum dweller was 23.04% of which prevalence of undiagnosed HTN was 16.03%. Significantly higher proportions of undiagnosed hypertensive were seen in males 22% and females 15.5% as well as also in all age groups, and it was seen twice in males as compared to females. The risk factor prevalence of current exposure to tobacco was 88.47% of which higher proportion, 90.7% was seen in females. Alcohol exposure was seen in 25% participants of which higher proportion, 38.5% seen in males and maximum exposure was seen in 46.7% males and 38.8% females and were from the young age group 18–30 years. Daily fruits and pure vegetarian diet consumption was observed in 3.2% and 19.3% slum dwellers, respectively. The prevalence of physical exercise was 17.1% of which significantly higher proportion, 22.0% was seen males and was of 1.8 times more than females. Overweight/obesity (body mass index >25 kg/m2) reported was 25.4% of which higher proportion, 26.9% was seen in females and they were maximum, 31.0% and 32.8% in males and females and from the age group of 40–50 years. Conclusion: Study revealed the prevalence of undiagnosed HTN at alarming state among the people residing in slum habitations. Similarly, risk factors such as tobacco, alcohol, physical inactivity, obesity, and dietary patterns were strongly existence among participants.